Merawat Asa Pendidikan: Implementasi Al-Islam dan Kemuhammadiyahan di Tengah Keterbatasan Pendidikan - Muslimah, Dewi Yuliati; Azani, Mohammad Zakki (Hikmah, 2023)
The availability of educators and facilities is a requirement for the achievement of educational goals, but unavailability is not one of the reasons for not implementing education. In this regard, this study aims to analyze the cultivation of Al-Islam and Kemuhammadiyahan values at SMP Muhammadiyah 6 Surakarta in the midst of limited facilities and educators. This research uses a case study-based qualitative research method. Data collection techniques used were observation, interview and documentation study. Data analysis used miles and huberman techniques, namely data collection, data reduction, data presentation, and conclusion drawing. The results of the study explain that the cultivation of Al-Islam and Kemuhammadiyahan values at SMP Muhammadiyah 6 Surakarta continues to run well despite its limitations. In terms of limited facilities and infrastructure, Al-Islam and Muhammadiyah learning is carried out outside the classroom such as courtyards and parks. In terms of media limitations, learning is carried out by optimizing the function of the blackboard. In terms of limited educators, the learning of Al-Islam and Muhammadiyah is concurrently assigned by the Islamic Education teacher.